Determining the influence of irradiation swelling on creep and damage in elements with orthotropic material properties - Breslavsky, Dmytro; Mietielov, Volodymyr; Tatarinova, Oksana (Eastern-European Journal of Enterprise Technologies, 2023)
This paper reports a method that numerically models the deformation and accumulation of hidden damage in structural elements that are in an inhomogeneous thermal field and are exposed to radiation. Materials considered are those exhibiting orthotropy (transversal isotropy) of long-term properties. The problem is stated as an boundary – initial value one. To solve it, the finite element method and the initial-difference method of time integration are used. To simulate the anisotropy of the process of accumulation of hidden damage, a damage tensor is applied. The development of irradiation swelling strains is described using the equation for a limited temperature range and a specific fluence value. The results of numerical modeling of creep and damage in plates in tension with circular notches, which are in an inhomogeneous temperature field, are considered. The material of the plates is a titanium alloy VT1-0. It was found that the effect of irradiation significantly, up to 6‒7 %, increases the level of deformation in the plate. Radiation significantly, by almost 4 times, reduces the time until the completion of the hidden fracture of the plates. It was found that orthotropy of radiation swelling properties leads to redistribution of areas with significant strains and damage values. It has been established that the effect of irradiation swelling also qualitatively changes the nature of the distribution of maximum damage in the plate, which extends to a fairly large area. Such results are due to the additional effect of irradiation swelling strains on the rate of general irreversible deformation and redistribution of stresses